The COVID-19 Pandemic Endangers Africa’s Indigenous Pygmy Populations - Fa, J.E.; Nasi, R.; Funk, S.M. (Springer, 2021)
Forest-dependent populations are affected by environmental pressures that include deforestation and forest degradation. Their lives and livelihoods have also been transformed by political decisions in the countries where they live. In Africa, the Pygmy peoples living in the dense tropical forests (4 million km2) that span west–east along the central African belt of the Congo Basin are made up of genetically and ethno-linguistically distinct groups (Bahuchet 2014). They are broadly subdivided into western groups, including Baka and Aka, and eastern groups including Mbuti, Efe, and Asua. All have a similar way of life associated with forest hunting and gathering even though some have taken up some form of agriculture. Additionally to their mode of subsistence, they share distinctive cultural and phenotypic traits such as the “Pygmy phenotype” of small adult body size (Perry and Dominy 2009). The demographic and evolutionary split between Pygmy and non-Pygmy populations is amongst the oldest for modern humans with the divergence estimated from genetic data to be roughly between 60,000 and over 100,000 years ago and the split between Western and Eastern Pygmy groups about 20,000 years ago (Hsieh et al. 2016). The Baka in south-eastern Cameroon, formerly strict hunters-gatherers, still practice a subsistence economy, but also maintain a close association with sedentary Bantu-speaking swidden agriculturalists with whom they have a complex social, economic, and symbolic relationship (Joiris 1998). Although less isolated than other Pygmy groups, especially the Mbuti and Efe, the Baka, like other forest-dependent populations in the Congo Basin, have been affected by a plethora of environmental pressures that include direct impacts from extractive industries (logging, mining), conflict with conservation areas, encroachment into their territories both peacefully along roads or aggressively by poachers and militias, as well as the effects of resettlement and sedentarization (Olivero et al. 2016). Such combination of threats impacts their health and food security. Currently, COVID-19 has reached Africa though apparently with an overall surprisingly low prevalence and mortality (Mbow et al. 2020). We argue that Pygmy communities may be silently ravaged by the disease yet there is a lack of policies or initiatives to monitor their health systematically throughout the Congo Basin. Understanding the impact of COVID-19 on these forest-dependent peoples has never been more important to develop ways of helping them.